2019
DOI: 10.3389/fimmu.2019.02921
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Landscape of Anti-Drug Antibodies Reveals the Mechanism of the Immune Response Following Treatment With TNFα Antagonists

Abstract: Drugs formulated from monoclonal antibodies (mAbs) are clinically effective in various diseases. Repeated administration of mAbs, however, elicits an immune response in the form of anti-drug-antibodies (ADA), thereby reducing the drug's efficacy. Notwithstanding their importance, the molecular landscape of ADA and the mechanisms involved in their formation are not fully understood. Using a newly developed quantitative bio-immunoassay, we found that ADA concentrations specific to TNFα antagonists can exceed ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…The mAb target may also have high importance for the MOA of ADA formation. We recently found that repeated administration of infliximab (a TNFα antagonist) results in a vaccine-like response, where ADA formation is governed by the extrafollicular T cell-independent immune response ( 96 ). The administration of infliximab blocks TNFα and shifts the immune response toward the marginal zone (MZ) instead of the germinal center (GC), as observed in TNFα knockout mice ( 97 ).…”
Section: Drug and Patient Characteristics Contributing To Ada Formatimentioning
confidence: 99%
See 1 more Smart Citation
“…The mAb target may also have high importance for the MOA of ADA formation. We recently found that repeated administration of infliximab (a TNFα antagonist) results in a vaccine-like response, where ADA formation is governed by the extrafollicular T cell-independent immune response ( 96 ). The administration of infliximab blocks TNFα and shifts the immune response toward the marginal zone (MZ) instead of the germinal center (GC), as observed in TNFα knockout mice ( 97 ).…”
Section: Drug and Patient Characteristics Contributing To Ada Formatimentioning
confidence: 99%
“…We recently reported on a newly developed quantitative bio-immunoassay for quantifying ADA specific to TNFα antagonists. The bio-immunoassay was further modified to easily assess the neutralization capacity of ADA using an in vitro assay ( 96 ). This assay can be readily used in a clinical setting that performs routine ADA measurements.…”
Section: Assays For Immunogenicity Assessment and Tools For Immunogenmentioning
confidence: 99%
“…Additionally, infusion reactions are associated with therapy discontinuation [ 38 ]. Systemic administration may induce anti-drug antibodies (ADA), which in turn is associated with infusion reactions as well as loss of efficacy [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…For sample collection, peripheral blood mononuclear cells (PBMCs) and total B cells have been generally used because of their accessibility. [ 9–11 ] However, because antibody repertoire properties are divergent between antigen‐specific B cells and plasma cells, [ 12 ] specific B cell populations or B cells located in targeted tissues should be enriched for more precise studies. Considering that as few as 2% of total B cells are circulating in peripheral blood, [ 13 ] this population can only provide a narrow view of the adaptive immune response to antigens; therefore, lymph nodes, spleen, and red bone marrow are preferential as the sources of B cells if accessible.…”
Section: Overview Of Ig‐seq Pipelinementioning
confidence: 99%